Analisis Pengelolaan Keuangan Desa dan Dampaknya Terhadap Social Capital Desa - Elga Agripta Aribowo; Andy Dwi Bayu Bawono (Prosiding, 2022)
This study aims to analyze village financial management and its impact on social capital. This research uses exploratory qualitative research methods.This research was conducted in Tanjung Village, Bendo District, Magetan Regency. Data collection techniques in this study using interviews, observation, library techniques and documentation techniques. The data analysis technique used was data adduction, data presentation and conclusion drawing.The results of the analysis show that (1) Tanjung Village Government apparatus in general are familiar with financial management and financial management principles, but the two village chief do not fully understand financial management. (2) There are indications that Social Capital in Tanjung Village still exists, but has decreased significantly after the enactment of Law Number 6 of 2014. (3) The reduced community participation in gotong royong is an obstacle and challenge faced by the Tanjung Village Government as for solutions offered by deliberation. (4) Based on the results of the analysis of the financial statements of the 2020 APBDes realization in Tanjung Village, it can be seen that the largest proportion of income is obtained from transfer income. (5) Based on the proportion of expenditure the largest use is used for goods and services expenditure. In addition, in the proportion of Sector Expenditures, the largest use is used for Expenditures for the Administration of Village Government. (6) Based on the calculation of the independence ratio, Tanjung Village can be said to have a low level of independence